Sustainable resort-related tourism growth: Identifying challenges and opportunities in Montalban, Rizal - Theresa Anne Nadine B. Lichauco (Goodwood Publishing, 2022)
Purpose: This study aims to identify the challenges and opportunities related to sustainable resort-related tourism growth in Montalban, Rizal, and the Philippines. Research Methodology: This study collected data from resort managers/operators and employees in Montalban using thematic analysis. The data were analyzed using systems theory to identify the interconnection of the economic, social, and environmental components of sustainable resort development. Results: The study found that resorts in Montalban are commercially viable, but environmental and social sustainability has been compromised since their founding and throughout the COVID-19 pandemic. The overexploitation of natural resources by resorts has led to concerns about groundwater level and water quality, while employees are subjected to precarious work and low income. Limitations: This study was limited by the sample size of the resorts in Montalban. Contributions: This study contributes to the current knowledge of sustainable resort-related tourism growth in rural destinations, particularly tourism destinations in the Philippines. This research seeks to educate policymakers, other tourism stakeholders, and local tourism communities on the need to shift their focus to more sustainable development. Novelty: This study pioneers the investigation of sustainability in resort-related tourism growth in the Philippines using the case of Montalban Rizal and the use of the system model in the qualitative study of sustainability in tourism destinations.